2019
DOI: 10.1111/jocn.14915
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care and management of patients’ sleep during hospitalisation: A cross‐sectional study

Abstract: Aim To explore and describe how patients’ sleep is addressed at acute‐care hospitals in Sweden with regard to nursing care, management and the development of knowledge in this area. Background Sleep is a basic human need and thus important for health and health maintenance. Patients describe sleeping in hospital as a stressor, and research shows that nurses tend to underestimate patients’ perceived problems with sleep during hospitalisation. How do nursing staff at acute hospitals address patients’ sleep and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…Although evidence has shown that non-pharmacological interventions can be effective in reducing sleep and circadian disturbances [8,9], organizational support to bring these practices to the bedside is unfortunately sparse [10], and most staff have reported not receiving formal education to manage these symptoms [11]. From previous work of authors, focus groups of multidisciplinary palliative care providers from three demographically diverse counties in New York State reported that "provision of educational interventions" was among the top recommendations to address sleep and circadian disturbances in individuals with advanced illness [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence has shown that non-pharmacological interventions can be effective in reducing sleep and circadian disturbances [8,9], organizational support to bring these practices to the bedside is unfortunately sparse [10], and most staff have reported not receiving formal education to manage these symptoms [11]. From previous work of authors, focus groups of multidisciplinary palliative care providers from three demographically diverse counties in New York State reported that "provision of educational interventions" was among the top recommendations to address sleep and circadian disturbances in individuals with advanced illness [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one important aspect in sleep assessment is that health care providers have insufficient knowledge about sleep. Fortunately, the problems are now being addressed, and several studies argue that sleep should be a topic included in nursing education and training [ 89 , 90 , 91 ].…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 99%
“…Then, a visual artificial intelligence nursing system is developed. It has functions of comparative management, query management, record management, nursing document management, basic settings, and basic nursing management, which are mainly realized through an APP end [ 12 , 13 ]. The system uses the design model of Model View Controller (MVC), the MyBatis framework, and other technologies [ 14 ].…”
Section: Introductionmentioning
confidence: 99%